Novel Intra‐Procedural Distensibility Measurement Accurately Predicts Immediate Outcome of Pneumatic Dilatation for Idiopathic Achalasia. (February 2018) - Wu, P I; Szczesniak, M M; Craig, P I; Choo, L; Engelman, J; Terkasher, B; Hui, J; Cook, I J
Abstract : OBJECTIVES: Often 2–3 graduated pneumatic dilatations (PD) are required to treat achalasia as there is no current intra‐procedural predictor of clinical response. Distensibility measurements using functional lumen imaging probe (FLIP) may provide an intra‐procedural predictor of outcome. Our aim was to determine the optimal criterion for esophagogastric junction (EGJ) distensibility measurements during PD that predicts immediate clinical response. METHODS: EGJ distensibility was prospectively measured using FLIP immediately pre‐ and post‐PD. The EGJ distensibility index (EGJ‐DI) was defined as a ratio of the narrowest cross‐sectional area and the corresponding intra‐bag pressure at 40 ml distension. Immediate and short‐term clinical responses were defined as Eckardt score ≤3 assessed 2 weeks Post‐PD and at 3‐month follow‐up, respectively. RESULTS: In 54 patients, we performed thirty‐seven 30 mm; twenty 35 mm and six 40 mm PDs. The short‐term response rate to the graded PD was 93% (27/29) in newly diagnosed achalasia; 87% (13/15) and 70% (7/10) in those who had relapsed after previous PD and Heller's Myotomy, respectively. Among those demonstrating an immediate response, EGJ‐DI increased by an average of 4.5 mm 2 /mmHg (95% CI (3.5, 5.5) ( P <0.001). Within‐subject Δ EGJ‐DI was highly predictive of immediate clinical response with AUROC of 0.89 (95% CI [0.80, 0.98], P <0.001). An increment in EGJ‐DI of 1.8 mm 2 /mmHg after a single PD predicts an immediate response with an accuracy of 87%. CONCLUSIONS: FLIP‐measured Δ EGJ‐DI is a novel intra‐procedural tool that accurately predicts immediate clinical response to PD in achalasia. This technique may potentially dictate an immediate mechanism to "step‐up" dilator size within a single endoscopy session.